REVIEW: PELUANG MAHKOTA DEWA SEBAGAI ANTIKANKER - Phebe Hendra (Universitas Sanata Dharma, 2012)
Abstract: In order to be used in formal health care systems, medicinal plants have to be safe and display promising pharmacological effects. Mahkota dewa is well known as a traditional medicine in Indonesia. In folk medicine, its fruits and leaves are used to relief cancer, impotency, hypoglycemic, hypotensive, antirheumatic, liver and kidney disorders and skin disorders. According to pharmacology and toxicology studies especially on cytotoxic effects, mahkota dewa has anticancer activity. However, further studies will be required to establish the cell target for anticancer treatment. Key words: mahkota dewa, anticancer, cytotoxic